Some considerations when teaching the tenses of Northern Sotho - Posthumus, L.C.; Mabule, M.S. (Journal for language teaching, 2002)
A shortcoming in standard grammars and other discussions of tense in Northern Sotho (and the other Bantu languages) is that very little or no attention is given to the role that temporal adverbials play in the interpretation of time reference. No discussion on tense in Northern Sotho is complete without a proper account of the role that temporal adverbials play in the interpretation of time and tense yet a systematic account of this influence of temporal adverbials is absent in all treatment of tense in Northern Sotho. The aim of this article is to disclose the importance of temporal adverbials in the interpretation of time reference in Northern Sotho. Every scholar of Northern Sotho (or any other Bantu language) should take proper cognisance of the prominent role that temporal adverbials play in establishing time reference. A clear distinction is drawn between tense and time. While tense is defined as the verb form that marks the relation between event time and speech / coding time, time is defined as an expression of the relation between event time and coding time which is superimposed on tense. The factors that have an influence on time interpretation are temporal adverbials, the semantic verb phrase categorization, tense, aspect and the text and / or context. The major time establishing device is the interrelation between tense forms and time adverbials. 'n Tekortkoming in die standaard grammatikas en ander besprekings van grammatiese tyd in Noord- Sotho (en die ander Bantutale) is dat geen of weinig aandag gegee word aan die rol wat temporeel adverbiale bepalings speel in die interpretasie van tyd. Geen bespreking van tyd in Noord-Sotho is volledig sonder 'n behoorlike verantwoording van die rol wat temporeel adverbiale bepalings speel in die interpretasie van (grammatiese) tyd en tempus nie. Nogtans ontbreek 'n sistematiese analise van die invloed van temporele adverbiale bepalings op tyd en tempus in alle besprekings van tyd in Noord-Sotho. Elkeen wat Noord-Sotho (of enige ander Bantutaal) bestudeer, behoort deeglik kennis te neem van die belangrike rol wat temporele adverbiale bepalings speel met betrekking tot tydverwysing. Die doel van hierdie artikel is om die belangrike rol te ondersoek wat die temporele adverbiale bepalings ten opsigte van tydinterpretasie in Noord-Sotho speel. 'n Duidelike onderskeid word getref tussen grammatiese tyd en tempus. Grammatiese tyd word gedefinieer as die werkwoordvorm wat die verhouding tussen gebeuretyd en spreek- / koderingstyd markeer terwyl tempus gedefinieer word as die uitdrukking van die verhouding tussen gebeuretyd en spreek- / koderingstyd ongeag die vorm van die werkwoord. Die faktore wat 'n invloed uitoefen op die interpretasie van tyd is: temporele adverbiale bepalings, die semantiese kategorisering van die werkwoordstuk, grammatiese tyd, aspek en die teks / konteks. Die deurslaggewende tempus-bepalende faktor is die interrelasie tussen tydvorme en temporele adverbiale bepalings.